Pemikiran Pragmatisme dalam Filsafat Pendidikan Islam Perspektif Kontemporer - Shodikun; M. Sugeng Sholehuddin (CV Edujavare Publishing, 2023)
The purpose of writing this work is to understand the concept of pragmatism thinking in Islamic educational philosophy from a contemporary perspective. library research method to analyze literature on pragmatism thinking and Islamic educational philosophy in the contemporary context. The main data sources include literature studies on pragmatism thinking from figures such as Peirce, James, and Dewey, as well as literature discussing the integration of pragmatism values in the Islamic education curriculum. In addition, the research will involve focused interviews with Islamic education experts or practitioners to gain direct views regarding the implementation of the concept of pragmatism in contemporary Islamic education. The result of this work, namely pragmatism thinking, makes a significant contribution by emphasizing the importance of concrete results, direct experience, and adaptability to the complexity of the times. The integration of pragmatism in learning methodology provides a relevant and effective foundation, balancing religious values with pragmatic needs. Active student collaboration, adaptation to local contexts, and methodological flexibility are key elements enriched by pragmatism thinking. In conclusion, pragmatism is not only a solution to the challenges of today's Islamic education but also a source of innovation that shapes learning methods